Pengaruh Penggunaan Teknologi Big Data dan Efisiensi Operasional Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar di BEI - Novi Aulia; Masnawaty Sangkala; Warka Syachbrani (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to determine the application of accounting records in Micro Enterprises at Warung kopi Konoha. This research method uses qualitative research methods, the variables of this study are the application of accounting in micro enterprises and the measurement of variables in this study is based on the preparation of SAK EMKM financial statements, the focus of this study is the application of accounting in the preparation of financial statements based on SAK EMKM and the subject of this study is the owner of Warung Kopi Konoha, with data collection techniques through observation, interview techniques, and documentation. Data analysis was carried out using qualitative descriptive analysis techniques. The results of the study show that Micro Enterprises at Warung Kopi Konoha experienced very positive developments from January to February 2025, from the financial position report side there was a total asset value in the February 2025 period of Rp. 175,172,958 and in the January period of Rp. 124,425,961 with a difference of Rp. 50,746,997. From the profit and loss statement side in the February 2025 period the profit generated was Rp. 100,823,479 and in the January period amounted to Rp. 48,705,479 with a difference of Rp. 50,118,000. And the Notes to the financial statements explain the summary of accounting policies and the measurement basis used in preparing the financial statements.